Determination of the Antioxidant Parameters of Commonly Available Black Pine (Pinus Nigra J.f. Arnold) (Bangladesh Journal of Botany, 2021)
The antioxidant parameters of black pine (Pinus nigra J.F. Arnold) needles samples collected from different areas in the province of Diyarbakır, Turkey were studied. Black pine needles samples were collected from three different locations (Egil, Kosuyolu, and Diyarbakır industrial area) in the province of Diyarbakır in summer and winter seasons. The activity of enzymatic antioxidants such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), glutathione S-transferase (GST) and malondialdehyde (MDA) levels of the samples were determined by ELISA method. Results showed that SOD enzyme activities of the samples collected in summer from Kosuyolu and the industrial area decreased compared to the control group, but increased in the samples collected in winter from the same areas. When compared to the control group, it was observed that the MDA levels of the samples collected from Kosuyolu and the industrial area increased.Bangladesh J. Bot. 50(4): 1021-1028, 2021 (December)`